IMPLEMENTASI PENDEKATAN CUSTOMER INTERFACE PADA MANAJEMEN PEMASARAN DI TOKO KOMPUTER - Ernatiningrum Ernatiningrum; Yusuf Sutanto (Politeknik Ubaya, 2018)
Conventional management has several weaknesses that must be covered so that the company can be grow. Therefore, trading companies try to analyze the constraints in the company’s expansion, namely marketing management with a customer interface approach. The factor that makes a company in using marketing management is the development of technology in this case information technology. With the existence of information technology customers can easily find the desired product in a store or company, customers can also compare expected products with similar products, customers can also request transactions electronically and request delivery of goods to the destination address with certain conditions and amounts. In addition, customers can easily see information about the item without having to go to the store. These advantages make use of information technology for business management so that trading companies can survive and anticipate the threat of similar companies in eroding the turnover of their business. This research will examine how the marketing process has been carried out by computer stores that have run management traditionally and electronically, how to design and develop marketing management to compete with similar companies. The purpose of this study was to find out the results obtained from utilizing information technology in management traditionally and electronically through interviews and surveys and thinking about how to develop marketing management to become the market leader in Central Java Province. The benefits of this research are so that it can be a consideration in determining good online marketing, as well as improving the quality of services that are better in increasing sales and expanding the sales area. The method used is marketing management with customer interfaces.